Aquatic animals inducing mechanical injuries - Haddad, Vidal [UNESP] (2016)
Injuries and envenomation are caused by poisonous, venomous, and traumatogenic aquatic animals. In this chapter we discuss the main aquatic animals that can cause trauma in humans, which are included in the Phyla Cnidaria (corals), Echinodermata (sea urchins), Crustacea (crabs and mantis shrimp) and Chordata (fish and reptiles), emphasizing the clinical aspects of the wounds and the therapeutical measures used to control the manifestations.